Innovations in Pharmacotherapy of Diabetes: A Review of Latest Reports - Czechowska, Katarzyna; Świerczewska, Aleksandra; Komasara, Piotr; Nowakowska, Julia; Sędek, Aleksandra; Merchel, Lena; Bednarek, Ilona; Lach, Sylwia; Błąd, Karol Seweryn; Kałuża, Kinga (Journal of Education, Health and Sport, 2025)
Introduction and purpose Diabetes mellitus as one of the most pressing global health challenges of the 21st century, affects millions worldwide and contributes significantly to mortality by damaging multiple organs and burdens healthcare systems. The global rise in diabetes, especially Type 2 is driven by lifestyle changes and aging populations. Diabetes impacts more than just blood sugar levels, leading to numerous complications that reduce quality of life. The review aims to explore the latest studies, innovations, and emerging possibilities in diabetes treatment. Material and methods The review was based on research of articles published from 2019 to 2025 on the PubMed database. The analysis summarizes recent trials, updated guidelines, and expert insights to highlight current trends and future directions in diabetes care. Results SGLT2 inhibitors help control blood sugar in type 2 diabetes and offer added benefits like weight loss, heart and kidney protection, and potential in treating NAFLD/NASH. GLP-1 receptor agonists also improve blood sugar, reduce cardiovascular risk, and slow kidney disease, with tirzepatide showing the greatest HbA1c and weight reductions. DPP-4 inhibitors, especially sitagliptin and vildagliptin, lower heart failure and stroke risk, though saxagliptin may raise heart failure risk. Pioglitazone improves PCOS outcomes and IVF success, and may help manage MASH when combined with SGLT2 inhibitors. Teplizumab, the first FDA-approved immunotherapy for type 1 diabetes, preserves insulin production by protecting β-cells. Conclusions Recent advances in diabetes treatment include updated guidelines promoting personalized care, new dual GIP/GLP-1 receptor agonists, and expanded use of SGLT2 inhibitors for heart and kidney protection. Research is also progressing in GLP-1 RAs for type 1 diabetes, immunotherapies like Teplizumab, and stem cell therapies aiming for a cure.